Cellulose‐supported N‐heterocyclic carbene silver complex with pendant ferrocenyl group for diaryl ether synthesis. (30th August 2016) - Jagadale, Megha; Salunkhe, Rajashri; Kumbhar, Arjun; Gajare, Shivanand; Rajmane, Mohan; Rashinkar, Gajanan
Abstract : A cellulose‐supported N‐heterocyclic carbene Ag(I) complex has been synthesized by covalent grafting of ferrocenyl ionic liquid in the matrix of cellulose followed by metallation with silver oxide. The complex was employed as a heterogeneous catalyst in the synthesis of diaryl ethers. Reactions of a variety of phenols with aryl halides afford corresponding diaryl ethers in moderate to good yields. Recyclability experiments were executed successfully for five consecutive runs. Abstract : Cellulose supported N‐heterocyclic carbene Ag(I) complex with pendant ferrocenyl group exhibits excellent catalytic performance in synthesis of diaryl ethers from aryl halides and structurally diverse phenols. Operational simplicity, clean reaction profile, reusability of catalyst, high TON and TOF are notable features of present protocol.